Age at Menopause and the Risk of Stroke: Observational and Mendelian Randomization Analysis in 204 244 Postmenopausal Women - Tschiderer, Lena; Peters, Sanne A. E.; van der Schouw, Yvonne T.; van Westing, Anniek C.; Tong, Tammy Y. N.; Willeit, Peter; Seekircher, Lisa; Moreno‐Iribas, Conchi; Huerta, José María; Crous‐Bou, Marta; Söderholm, Martin; Schulze, Matthias B.; et al. (Journal of the American Heart Association, 2023)
Background Observational studies have shown that women with an early menopause are at higher risk of stroke compared with women with a later menopause. However, associations with stroke subtypes are inconsistent, and the causality is unclear. Methods and Results We analyzed data of the UK Biobank and EPIC-CVD (European Prospective Investigation Into Cancer and Nutrition-Cardiovascular Diseases) study. A total of 204 244 postmenopausal women without a history of stroke at baseline were included (7883 from EPIC-CVD [5292 from the subcohort], 196 361 from the UK Biobank). Pooled mean baseline age was 58.9 years (SD, 5.8), and pooled mean age at menopause was 47.8 years (SD, 6.2). Over a median follow-up of 12.6 years (interquartile range, 11.8-13.3), 6770 women experienced a stroke (5155 ischemic strokes, 1615 hemorrhagic strokes, 976 intracerebral hemorrhages, and 639 subarachnoid hemorrhages). In multivariable adjusted observational Cox regression analyses, the pooled hazard ratios per 5 years younger age at menopause were 1.09 (95% CI, 1.07-1.12) for stroke, 1.09 (95% CI, 1.06-1.13) for ischemic stroke, 1.10 (95% CI, 1.04-1.16) for hemorrhagic stroke, 1.14 (95% CI, 1.08-1.20) for intracerebral hemorrhage, and 1.00 (95% CI, 0.84-1.20) for subarachnoid hemorrhage. When using 2-sample Mendelian randomization analysis, we found no statistically significant association between genetically proxied age at menopause and risk of any type of stroke. Conclusions In our study, earlier age at menopause was related to a higher risk of stroke. We found no statistically significant association between genetically proxied age at menopause and risk of stroke, suggesting no causal relationship.